Theorising women's health and health inequalities: shaping processes of the 'gender-biology nexus' - Ellen Annandale; Maria Wiklund; Anne Hammarström (Taylor & Francis Group, 2018)
Since the theoretical frameworks and conceptual tools we employ shape research outcomes by guiding research pathways, it is important that we subject them to ongoing critical reflection. A thoroughgoing analysis of the global production of women's health inequality calls for a comprehensive theorization of how social relations of gender and the biological body mutually interact in local contexts in a nexus with women's health. However, to date, the predominant concern of research has been to identify the biological effects of social relations of gender on the body, to the relative neglect of the co-constitutive role that these biological changes themselves may play in ongoing cycles of gendered health oppressions. Drawing on feminist and gender theoretical approaches, and with the health of women and girls as our focus, we seek to extend our understanding of this recursive process by discussing what we call the 'shaping processes' of the 'gender-biology nexus' which call attention to not only the 'gender-shaping of biology' but also the 'biologic-shaping of gender'. We consider female genital mutilation/cutting as an illustration of this process and conclude by proposing that a framework which attends to both the 'gender-shaping of biology' and the 'biologic-shaping of gender' as interweaving processes provides a fruitful approach to theorising the wider health inequalities experienced by women and girls.